Stability and Control of Retracement Channels in Thin Seam Working Faces with Soft Roof - Binbin Qin; Fulian He; Xiaobing Zhang; Xuhui Xu; Wei Wang; Liang Li; Chen Dou (Shock and Vibration)
To reduce the risk of roof falling and rib spalling during equipment retracement in thin coal seam faces with soft roofs, the 25070 working face of Xuehu Coal Mine was taken as the research object, and theoretical analysis, numerical simulation, and field practice methods were used. Under different space relationships between retracement channels and main roof fracture, the load of hydraulic supports was quantitatively analyzed. The relationship between the working resistance of the hydraulic support and the sinking rotation angle of the immediate roof was analyzed, and a reasonable time for the arrangement of the retracement channel was determined. The sublevel excavation technology and the combined support technology of roof anchor cables and coal rib anchors were proposed. The field application shows that the falling height and rate of movable prop of the hydraulic supports, working resistance of the hydraulic supports, and the roof subsidence all meet the requirements of safety production during the terminal mining period, and the surrounding rock control effect of retracement channel was determined to be good. The safe and efficient mining of the coal mine is ensured, and the research results can provide guidance for similar working faces.